2018
DOI: 10.21037/mhealth.2018.11.02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the patient experience with urological video visits at an academic medical center

Abstract: Background: Telemedicine utilization, including use of video visits, is growing rapidly. While much enthusiasm surrounds telemedicine, the successful implementation of video visits within health systems requires providers to evaluate patient's experience with the implemented technology and workflow. Methods: Twenty patients who completed a video visit in the Department of Urology at Michigan Medicine were contacted and asked if they would be willing to share their experience. Patients underwent a semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Prior researchers have demonstrated the value of urologic video visits in an outpatient setting and studies have confirmed that telehealth is not only a safe alternative to urologic clinic visits but also cost-effective, more efficient for patients, and with high patient satisfaction. 10,[22][23][24] While the overall revisit rate for clinic encounters was higher than video visits in our study, this difference was primarily driven by previously scheduled appointments. When we compared the clinically relevant revisit rate, we found no difference between video and clinic visits.…”
Section: Discussionmentioning
confidence: 53%
“…Prior researchers have demonstrated the value of urologic video visits in an outpatient setting and studies have confirmed that telehealth is not only a safe alternative to urologic clinic visits but also cost-effective, more efficient for patients, and with high patient satisfaction. 10,[22][23][24] While the overall revisit rate for clinic encounters was higher than video visits in our study, this difference was primarily driven by previously scheduled appointments. When we compared the clinically relevant revisit rate, we found no difference between video and clinic visits.…”
Section: Discussionmentioning
confidence: 53%
“…Video visits have been reported in other surgical subspecialties [19][20][21]. However, realtime video interactions for ophthalmic visits have not previously been described, and video visits had not previously been offered by our department.…”
Section: Video Visitsmentioning
confidence: 98%
“…Our findings are consistent with prior studies comparing patient-reported satisfaction telehealth visits to in-person visits across non-otolaryngologic surgical subspecialties. 3,[7][8][9] The application of telemedicine in otolaryngology has evolved over time. Studies from the 1990s demonstrated successful pairing of otolaryngologists with general practitioners in remote areas with limited access to specialty surgical care.…”
Section: Discussionmentioning
confidence: 99%
“…While telemedicine has historically been associated with high levels of patient satisfaction, 3,[6][7][8][9] many of these studies have not previously incorporated the use of validated patient satisfaction surveys into their study design. Furthermore, several recently published commentaries in the otolaryngology literature have outlined the broad implementation of telemedicine during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%